2022
DOI: 10.1002/jcop.22829
|View full text |Cite
|
Sign up to set email alerts
|

Weathering the storm alone or together: Examining the impact of COVID‐19 on sole and partnered working mothers

Abstract: Sole employed mothers and their families face numerous challenges. Yet, the unprecedented circumstances of the COVID‐19 pandemic may be adding additional risk to the already precarious day‐to‐day reality of this population. Thus, we examine the implications of this crisis for the mental health and job‐related well‐being of both sole and partnered working mothers. Participants were 206 mothers who continued to work during the pandemic. A moderated mediation model was analyzed. Work‐family conflict (WFC) during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…As a consequence of a high strain on work-family conflict, a decrease in physical and mental health dimensions among women (including stress, anxiety, and depression symptoms) was reported in this study, as well as in previous research [ 19 , 23 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Both studies by Oakman et al [ 41 ] and Graham et al [ 39 ] showed that Australian working women reported significantly greater WFC and FWC, and concerns about job insecurity, stress, and neck/shoulder pain compared to men.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As a consequence of a high strain on work-family conflict, a decrease in physical and mental health dimensions among women (including stress, anxiety, and depression symptoms) was reported in this study, as well as in previous research [ 19 , 23 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Both studies by Oakman et al [ 41 ] and Graham et al [ 39 ] showed that Australian working women reported significantly greater WFC and FWC, and concerns about job insecurity, stress, and neck/shoulder pain compared to men.…”
Section: Discussionsupporting
confidence: 88%
“…Compared to men, women were more responsible for childcare, schooling, and household tasks, working primarily from home and reducing their work hours [ 19 , 23 , 34 , 35 , 36 , 37 ]. Overload in caregiving and overall workload in women was related to heightened WFC and FWC, as well as parenting stress, general perceived stress, concerns about job insecurity, general and neck/shoulder pain, stress, depressive and anxiety symptoms, and lower life satisfaction [ 19 , 23 , 24 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In particular, solely employed mothers were at higher risk of mental health adverse effects and job-related well-being than partnered working mothers [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article by Dionisi et al (2023) the aim of this research was to begin to understand how the COVID‐19 crisis impacted the lives of working mothers which included examining their level of mental health and job‐related well‐being. The authors used the lens of conservation resources to examine how work‐family conflict may impact a mother's experiences of parenting depending on their romantic relationship status.…”
mentioning
confidence: 99%
“…Strains include adverse outcomes such as burnout, job stress, depression, and somatic complaints (Copranzano et al, 1997;Armstrong-Stassen, 2004;Richardson et al, 2008;Servat et al, 2020). Similarly, stressors include a range of challenges faced by employees in the workplace, such as role conflict, work overload, organizational politics (Kurtessis et al, 2017), and, in the COVID-19 context in particular, family-related challenges, such as balancing work and family care (Dionisi et al, 2022), and health-related challenges, such as contracting the virus (Hamouche, 2020) and accessing healthcare (Auerbach & Miller, 2020).…”
Section: Objective and Contributionsmentioning
confidence: 99%